1985
DOI: 10.1111/j.1469-8137.1985.tb02873.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Removal of Extraradical Hyphae on Water Uptake by Vesicular‐arbuscular Mycorrhizal Plants

Abstract: SUMMARYResults from experiments on clover (Trifoliumpratense L.) and leek (Alliumporrum L.) revealed that removal of extraradical hyphae from vesicular-arbuscular mycorrhizal (VAM) plants had a detrimental effect on transpiration flux. The advantage of comparisons between VAM plants with and without extraradical hyphae rather than between VAM and non-mycorrhizal plants is discussed in relation to this type of investigation. It is suggested that extraradical hyphae increase the root absorptive-surface area, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 21 publications
3
52
0
1
Order By: Relevance
“…The capacity of hyphae to Canada to Line Lapomte. absorb significant water volumes is questioned by some authors (Levy & Krikun, 1980;Fitter, 1988) REEERENCES but is supported by others (Hardie, 1985;Faber, . ",, …”
Section: Effects Of the Presence Of Mycorrhizas On Plant Growth Undermentioning
confidence: 99%
“…The capacity of hyphae to Canada to Line Lapomte. absorb significant water volumes is questioned by some authors (Levy & Krikun, 1980;Fitter, 1988) REEERENCES but is supported by others (Hardie, 1985;Faber, . ",, …”
Section: Effects Of the Presence Of Mycorrhizas On Plant Growth Undermentioning
confidence: 99%
“…At the lowest moisture level (0.6 FC) the fungus Ge was more efficient than Gm in maintaining high leaf RWC (Figs 1, 2). Hardie (1985) reported that AM fungal hyphae with a diameter of 2-5 µm can penetrate soil pores inaccessible to root hairs (10-20 µm diameter) and so absorb water that is not available to non-mycorrhizal plants. Faber et al (1991) measured rates of water transport by AM fungal hyphae ranging from 375 to 760 nL H 2 O h −1 .…”
Section: Relative Water Contentmentioning
confidence: 99%
“…It is now accepted that the contribution of AM symbiosis to plant drought tolerance is the result of accumulative physical, nutritional, physiological and cellular effects (Ague, 2001). The pioneer studies of Allen (1982) and Hardie (1985) indicated a possible role of AM fungal in water uptake and transfer to the host plant. Allen (1991) estimated that the rate of water transport by extraradical hyphae to the root was 0.28 ng s −1 per entry point, a level sufficient to modify plant water relations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the possibility of direct hyphal contributions to root water uptake (Hardie 1985;Faber et al 1991;Ruiz-Lozano and Azcón 1995), soil hyphae may increase soil-to-root contact in drying soils (e.g., Reid 1979;Fitter 1985;Davies et al 1992). Root and soil shrinkage creates gaps between the root and the soil, which can decrease water absorption (e.g., Nobel and Cui 1992).…”
Section: Testing Contributions Of Soil Andmentioning
confidence: 99%